MEMPERTAHANKAN TANAH AIR PALESTINA PADA PUISI “QAṢĪDATU AL-ARḌI” DALAM ANTOLOGI AL-AʻMĀLU AL-KĀMILATU KARYA MAḤMŪD DARWĪSY ANALISIS SEMIOTIK - Ridhotun Ni’mah (Arabic Literature Department, 2019)
The condition of Palestine which has been occupied by Israel for a long time and has yet to be resolved, encourages poets to give birth to literary works in which echoed the suffering experienced by the Palestinian people. One of them is the poem of Maḥmūd Darwīsy entitled